The Evolution of Local Human Civilizations and the Problem of the Proliferation of Standards in International Relations - A. Kazantsev; S. Medvedeva (Международная аналитика)
The article contains prognosis of development of local human civilizations in the regions of world neighboring to Russia (Europe, Islamic world, Asia-Pacific region). This issue is analyzed from the point of view of proliferation of norms within the system of international relations, which is the process playing a key role from the point of view of guaranteeing robustness of this system. The main conclusion of the paper is that the speed of norm proliferation within the system of international relations in the 21 century will be checked by a set of factors. First, the dynamic of development of Europe and the USA indicates a clear tendency towards decrease of unifying potential that has appeared originally as a result of influence of the Western world towards other local human civilizations. Second, the study of development of Islamic civilization indicates that there is a significant potential of rejection of unification of norms within the system of international relations. Third, analysis of the group of local human civilizations existing in the Asia-Pacific region demonstrates that economic development of this region is accompanied by formation of ideas about cultural norms alternative to Europe-centric world.